Caracterização molecular dos sorotipos da dengue e correlação dos índices pluviométricos e dos casos de dengue na Paraíba, no período de 2007-2015 - Gomes, Isabel Cristina Guerra (2016)
Dengue belongs to the Flaviviridae family, genus Flavivirus and is a mosquito-borne viral infection. Dengue can be originated by any of the four DENV serotypes that can be categorized into: DENV-1, DENV-2, DENV-3, and DENV-4. The major vector is Aedes aegypti alongside with Aedes albopictus, and the spreading of dengue is attributed to the expansion in the niche of the vectors as well as by the global trade and travel increase, unplanned urbanization, and bad management of waste and water. Consequently, climate is considered an important factor in the temporal and spatial distribution of vector borne diseases. Despite being the most prevalent arbovirus disease worldwide, dengue has been neglected in the last years. Only through recent epidemic profile outbreaks of different arboviruses, such as zika (ZIKV) and chikungunya (CHIKV) all around the world promoted an alert to health authorities towards those diseases. Thus, this study evaluated the clinical characteristics and classification obtained from Information System for Notifiable Diseases (SINAN) reporting files. The monthly incidence of dengue cases was calculated by year/100,000 inhabitants. The detection and genotyping of DENV was done using nested RT–PCR, between 2007-2015, and in 2016 differentiation diagnostic was performed with real time PCR (qPCR) for ZIKV and CHIKV. Besides, this study evaluated the correlation between rainfall precipitation and dengue cases from 2007 to 2015, in João Pessoa-PB, Brazil Northeast. Data of rainfall were collected monthly through TRMM probe. In order to identify the influence of rainfall and dengue cases different distributed lag models were considered. Concerning the period of 2007 to 2015, results showed 55680 confirmed cases of dengue were reported in Paraiba. There was a higher prevalence of infection in patients aged between 15-34 years in all studied years. Our results demonstrated that the correlation (r ˃0.50) between rainfall and dengue cases occurrence increased in the first months after the rainy season, presenting more significant results considering a lag of three months. DENV 1 was the most identified virus (80.48%) in all studied years and co-circulation of the four DENV serotypes was observed in 2010, 2013 and 2014. Furthermore, we observed the simultaneous circulation of dengue, zika and chikungunya cases in 2016, and demonstrated a predominance of zika cases followed by chikungunya cases. Therefore, molecular characterization and correlation of dengue cases and rainfall data analyses may be useful for the future development of prediction technology towards dengue cases as well as others arboviruses, such as zika and chikungunya.